Interpreting the Quina and demi-Quina scrapers from Acheulo-Yabrudian Qesem Cave, Israel: Results of raw materials and functional analyses. Issue 144 (July 2020) - Agam, Aviad; Zupancich, Andrea
Abstract: Quina scrapers are well-known components of the European Middle Paleolithic Mousterian. A similar production process was detected within the lithic assemblages of the Levantine Acheulo-Yabrudian (∼400–200 ka). This study combines the results of use-wear and raw material analyses of 75 Quina scrapers and 133 demi-Quina scrapers from the Acheulo-Yabrudian site Qesem Cave, Israel, aimed at interpreting the function of Quina and demi-Quina at Qesem Cave, the considerations affecting the lithic choices involved in their production, and the behavioral and evolutionary implications. Each scraper was examined for use-wear and was assigned to a flint type and potential geologic source(s). Our results demonstrate a selective pattern of exploitation of flint which does not originate from the local Turonian outcrops, specifically for the manufacture of Quina and demi-Quina scrapers. This suggests a thoughtful, well-planned effort, taking into consideration the flint traits and future function. This pattern repeats itself throughout time, reflecting a high degree of familiarity with the potential sources located around the cave, implying the existence of knowledge transmission mechanisms concerning the location of specific flint sources and their acquisition methods, as well as concerning exploitation preferences.